Local auxin metabolism regulates environment-induced hypocotyl elongation - Zheng, Zuyu; Guo, Yongxia; Novák, Ondřej; Chen, William; Ljung, Karin; Noel, Joseph P; Chory, Joanne (Nature plants, 2016)
A hallmark of plants is their adaptability of size and form in response to widely fluctuating environments. The metabolism and redistribution of the phytohormone auxin play pivotal roles in establishing active auxin gradients and resulting cellular differentiation. In Arabidopsis thaliana, cotyledons and leaves synthesize indole-3-acetic acid (IAA) from tryptophan through indole-3-pyruvic acid (3-IPA) in response to vegetational shade. This newly synthesized auxin moves to the hypocotyl where it induces elongation of hypocotyl cells. Here we show that loss of function of VAS2 (IAA-amido synthetase Gretchen Hagen 3 (GH3).17) leads to increases in free IAA at the expense of IAA-Glu (IAA-glutamate) in the hypocotyl epidermis. This active IAA elicits shade- and high temperature-induced hypocotyl elongation largely independently of 3-IPA-mediated IAA biosynthesis in cotyledons. Our results reveal an unexpected capacity of local auxin metabolism to modulate the homeostasis and spatial distribution of free auxin in specialized organs such as hypocotyls in response to shade and high temperature.
Keywords: down regulace; Temperature; Genes, Plant; životní prostředí; mutace; Biosynthetic Pathways; RNA, Plant; Arabidopsis; Glucuronidase; Environment; kyseliny indoloctové; kotyledon; biosyntetické dráhy; regulace genové exprese u rostlin; epidermis rostlin; hypokotyl; biologický transport; Down-Regulation; Indoleacetic Acids; Gene Expression Regulation, Plant; glukuronidasa; Hypocotyl; teplota; rostlinné geny; Mutation; Plant Epidermis; Cotyledon; RNA rostlin; Biological Transport